(untitled) (Research, Society and Development, 2022)
Introduction: despite efforts in recent decades, the global burden of schistosomiasis still remains high. This may in part be linked to the lack of accurate diagnostic tools to detect schistosome infections in humans and animals in endemic areas. Objective: to identify in the scientific literature new laboratory techniques for the diagnosis of schistosomiasis. Thus, the methodology was an integrative review study. For the development, searches were carried out in the following databases: Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMed), Latin American and Caribbean Literature on Health Sciences (LILACS), Scopus, in addition to the Databases of the International Medical and Biomedical Literature (MEDLINE). From the search results in the databases, 366 articles were selected, in addition to theses and dissertations. After reading the abstracts, 25 articles remained for the development of the study. The improvement of methods for the diagnosis of schistosomiasis to obtain better results and, at the same time, search for new diagnostic markers, such as Aquaporin, Dysferlin and rSm200, which are viable biomarkers for diagnosis, which can be used for the development of rapid tests and contribute to increase the accuracy of the analysis. Conclusion: we found that the development and implementation of effective diagnostic methodologies is crucial in all aspects of schistosomiasis control. New schistosomiasis diagnostic technologies are largely based on nucleic acid amplification and can compensate for the shortcomings of traditional parasitic methods. However, isothermal amplification techniques have advanced significantly in the diagnosis of schistosomiasis.